Regional Versus Individual Aspects of the Digital Divide in Germany - Katrin Schleife (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2008)
This paper analyzes the regional dimension of the German digital divide. It studies the determinants of home Internet use in Germany on the level of counties as well as on the level of individuals. Based on two large data sets, the analyses show that population density itself cannot explain regional differences in Internet use rates. The results rather indicate that it is the different composition of individual characteristics between rural and urban populations that accounts for the regional digital divide. At individual level, the findings underline the importance of network effects.
Older version: http://hdl.handle.net/10419/24540
Keywords: R20; O18; O33; 330; digital divide; Internet use; network effects; Internet; Medienverhalten; Regionale Disparität; Stadt-Land-Beziehung; Bildungsniveau; Deutschland